Упростите ( tg(180° - а)*cos(180° - а)*tg(90° - а) ) / ( sin(90° + а)*ctg(90° -...

0 голосов
75 просмотров

Упростите
( tg(180° - а)*cos(180° - а)*tg(90° - а) ) / ( sin(90° + а)*ctg(90° - а)*tg(90° + а) )


Алгебра | 75 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

\frac{tg(180- \alpha) * cos(180- \alpha )*tg(90- \alpha )}{sin(90+ \alpha)*ctg(90- \alpha )*tg(90+ \alpha )} = \frac{-tg\alpha * (-cos\alpha )*ctg \alpha }{cos \alpha*tg \alpha *(-ctg\alpha )} = -1
(6.8k баллов)
0 голосов
( tg(180° - а)*cos(180° - а)*tg(90° - а) ) / ( sin(90° + а)*ctg(90° - а)*tg(90° + а) ) = ( sin(180° - а)*tg(90° - а) ) / ( sin(90° + а)*ctg(90° - а)*tg(90° + а) ) =
( sin(а)*ctg(а) ) / ( (cos(а))*tg(а)*(-ctg( а) )) = (cos(а))/(-cos(а)) = -1
(140 баллов)